Treating Autoimmune-Related Interstitial Lung Disease With B Cell Depletion - Liossis, Stamatis-Nick C.; Bounia, Constantina A. (Frontiers in Medicine, 2022)
Autoimmune rheumatic diseases may affect vital organs with lung involvement being a severe and difficult to treat manifestation. Systemic sclerosis (SSc) commonly affects the lung in the form of interstitial lung disease (ILD). ILD may be also seen in patients with rheumatoid arthritis (RA), Sjögren’s syndrome (SS), systemic lupus erythematosus (SLE), inflammatory myositis (IM), antisynthetase syndrome (AS) and the ANCA-associated vasculitides (AAV). Rituximab (RTX) is an anti-CD20 B lymphocyte depleting mAb often administered in the treatment of autoimmune rheumatic diseases. Although RTX is an off-label treatment for CTD - ILD, there are numerous reports providing data that is effective in improving both pulmonary function tests (PFTs) and chest computed tomography findings consistent with ILD. There are retrospective uncontrolled studies that assess RTX as a treatment of ILD in autoimmune diseases. These studies, apart from one, do not include patients with AAV-ILD. In SSc-ILD in particular, there are both controlled and uncontrolled studies displaying encouraging results following B cell depletion. In addition, a number of retrospective uncontrolled studies and fewer prospective studies evaluate RTX in connective tissue diseases CTD - ILD. Although RTX is an approved treatment for AAV there are scarce only data focusing in patients with AAV-ILD specifically. The results of a handful of studies comparing treatment of CTD-ILD with RTX to treatment with other agents are in favour of RTX. Results from large, still ongoing controlled trials are awaited to ascertain RTX effects in ILD encountered in autoimmune rheumatic diseases. We review herein the results of the different RTX trials in patients with autoimmune disease – associated ILD. Despite the heterogeneity of these studies, RTX may be considered as an alternative and safe but still off-label treatment for patients with refractory CTD–ILD.